Preparation method of low-deformation modified epoxy insulating I-shaped steel

Through the combination of epoxy resin, liquid anhydride and benzoxazine resin and pultrusion process, a dense interpenetrating network structure is formed, which solves the problems of large deformation and insufficient rigidity of epoxy insulated I-shaped steel, and achieves low deformation and high precision product preparation.

CN120463994APending Publication Date: 2025-08-12SICHUAN D&F ELECTRICAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510710594.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-29
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

In the preparation of low-deformation modified epoxy insulated I-shaped steel, the epoxy resin cross-linking reaction is insufficient, volume shrinkage and internal stress are difficult to control, resulting in large deformation of the product and difficult to meet the needs of high-precision applications.

Method used

The combination of epoxy resin, liquid anhydride and benzoxazine resin is adopted to form a dense interpenetrating network structure through high-speed mixing and pultrusion processes, combining specific curing temperatures and speeds, which inhibit volume shrinkage and internal stress and control product deformation.

Benefits of technology

It effectively reduces the deformation of modified epoxy insulated I-shaped steel, improves the rigidity and dimensional accuracy of the product, and meets the needs of high-precision applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120463994A_ABST
    Figure CN120463994A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of low-deformation modified epoxy insulating I-shaped steel, and the preparation method of the low-deformation modified epoxy insulating I-shaped steel comprises the following steps: A, preparing a component A; the preparation method comprises the following steps: adding epoxy resin, liquid anhydride, benzoxazine resin and an organic silicon release agent into a high-speed mixer according to a weight ratio of 100: (85-105): (45-55): 1.5, and uniformly mixing to obtain a resin glue solution; b, the resin glue solution is poured into a constant-temperature dipping tank of pultrusion equipment, and after glass fibers are drawn to be dipped in resin, the glass fibers sequentially pass through a pre-forming mold and a curing mold; and C, cooling the product to room temperature to obtain the modified epoxy insulating I-shaped steel. Compared with a traditional mold pressing process, the method has the advantages that the component proportion is combined with the pultrusion process, the specific curing mode and other process means, the method has more advantages in the aspects of fiber dipping uniformity, stress control in the curing process, overall product size precision control and the like, product deformation can be more effectively restrained, and the product is more excellent in deformation control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of epoxy insulation material preparation, and in particular relates to a method for preparing low-deformation modified epoxy insulation I-steel. Background Art

[0002] With the continuous development of modern industry, epoxy insulated I-beams have a wide range of application demands in many fields, such as electrical equipment, rail transportation, and aerospace industries. Because it combines insulation properties with good structural support, it has become one of the key materials to ensure the safe and stable operation of various devices. In terms of its preparation, the industry has been committed to improving the comprehensive performance of the product by optimizing the raw material formula and improving the process, especially the control of product deformation, because lower deformation means higher dimensional accuracy and better stability in use, which is crucial for high-precision assembly and long-term reliable operation application scenarios. At present, researchers have tried a variety of different resin systems, additives and processing technologies to explore how to reduce the deformation of epoxy insulated I-beams during curing and subsequent use, and have made some progress, but still face many challenges.

[0003] The existing technology still has obvious deficiencies in the preparation of low-deformation modified epoxy insulated I-beams. On the one hand, in terms of material formulation, during the cross-linking and curing process of traditional epoxy resin systems, it is often difficult to accurately control the amount of liquid anhydride used, resulting in insufficient cross-linking reaction of the epoxy resin and the inability to form a dense and stable cross-linked network structure. This makes the overall rigidity of the product insufficient and it is difficult to effectively resist internal stress, which in turn causes a large amount of product deformation. At the same time, there is a lack of effective modifying ingredients in the formula to inhibit the volume shrinkage of the epoxy resin during curing, the internal stress problem is difficult to solve, and the deformation control effect is poor. On the other hand, from a process perspective, the traditional molding process that is widely used has many limitations. It is difficult to ensure uniformity in the fiber impregnation link, stress control during the curing process is not ideal, and the ability to control the overall dimensional accuracy of the product is poor, resulting in the product being prone to large deformation after molding and unable to meet the requirements of high-precision application scenarios.

[0004] Patent application number CN202411968537.7 discloses a two-liquid high-voltage resistant epoxy insulating casting resin and its preparation method, which uses a two-component mixing process. For component A, the mixing temperature is 70-80°C for 150-180 minutes, and for component B, the mixing temperature is 85-95°C for 100-120 minutes. Under these process conditions, the temperature range and time setting may result in the inability to fully and evenly mix the raw materials or excessive mixing, which may affect the performance of the raw materials. For example, if the temperature is too low, some high-melting-point, high-viscosity raw materials may not be well dispersed and may easily form local agglomerations, affecting the quality of the final product; and if the time is too long, some heat-sensitive raw materials may decompose or degrade, thereby affecting the overall performance stability of the casting resin. Summary of the Invention

[0005] The object of the present invention is to provide a method for preparing a low-deformation modified epoxy insulated I-beam to solve the following technical problems raised in the background technology:

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0007] A method for preparing a low-deformation modified epoxy insulated I-beam comprises the following steps:

[0008] A. Add epoxy resin, liquid acid anhydride, benzoxazine resin and silicone release agent in a weight ratio of 100 parts: 85-105 parts: 45-55 parts: 1.5 parts into a high-speed mixer and mix well to obtain a resin glue solution;

[0009] B. Pour the resin glue into the constant temperature impregnation tank of the pultrusion equipment, pull the glass fiber to be impregnated with resin, and then pass it through the preforming mold and curing mold in sequence;

[0010] C, cooling the product to room temperature to obtain a modified epoxy insulated I-steel.

[0011] Furthermore, the epoxy resin is any one of E51, CYD128, and E54, or a mixture of any two of them in any ratio.

[0012] Furthermore, the liquid acid anhydride is any one of methyltetrahydrophthalic anhydride and methylnadic anhydride, or a mixture of the two in any ratio.

[0013] Furthermore, the benzoxazine resin is any one of a phenol-type benzoxazine resin and a bisphenol A-type benzoxazine resin, or a mixture of the two in any ratio.

[0014] Furthermore, the temperature of the constant temperature immersion tank is 55°C ± 3°C.

[0015] Furthermore, the mold curing temperature is 180±10°C.

[0016] Furthermore, in step B, the pultrusion speed is 100±20 mm / min.

[0017] Furthermore, the deformation of the modified epoxy insulated I-beam is 1.7-3.0 mm.

[0018] Furthermore, before pouring the resin glue into the constant temperature dipping tank of the pultrusion equipment, the high-speed mixer is vacuumed to maintain the pressure in the mixer between -0.08 MPa and -0.06 MPa.

[0019] Furthermore, in step A, the rotation speed of the high-speed mixer is 1200-1500 r / min, and the mixing time is 5-8 minutes.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] In the present invention, an appropriate amount of liquid anhydride can make the cross-linking reaction of the epoxy resin more complete, thereby forming a denser and more stable cross-linked network structure, effectively improving the overall rigidity of the product, and enabling the product to better resist internal stress during curing and subsequent use, thereby reducing deformation.

[0022] In the present invention, an appropriate amount of benzoxazine resin is added to form an interpenetrating network structure with the epoxy resin, which can significantly inhibit the volume shrinkage of the epoxy resin during curing and reduce the internal stress generated by shrinkage, thereby achieving a better effect of controlling product deformation.

[0023] The pultrusion process adopted in the present invention is combined with specific curing methods and other process means. Compared with the traditional molding process, it has more advantages in terms of fiber impregnation uniformity, stress control during the curing process, and overall dimensional accuracy control of the product. It can more effectively suppress product deformation and make the product more excellent in deformation control. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION

[0025] The following will provide a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0026] Example 1:

[0027] A method for preparing low-deformation modified epoxy insulation I-beam, such as Figure 1 As shown, the following steps are included:

[0028] A, E51 epoxy resin, methyltetrahydrophthalic anhydride, phenolic benzoxazine resin and paraffin are added into a high-speed mixer in a weight ratio of 100 parts: 85 parts: 45 parts: 1.5 parts, and mixed at a speed of 1200-1500 r / min for 5-8 minutes to obtain a uniform resin glue solution.

[0029] B. Pour the resin glue into the 55℃ constant temperature impregnation tank of the pultrusion equipment. After the glass fiber is impregnated with resin at a pulling speed of 100mm / min, it passes through a scraping type pre-forming mold with a gap of 1.2-1.8mm and a 180℃ curing mold in sequence.

[0030] C, naturally cooling the product to room temperature to obtain a modified epoxy insulated I-steel.

[0031] The deformation of modified epoxy-insulated I-beams was tested using the following method: 1200mm long specimens were simply supported across a 1000mm span. The mid-span deflection was measured using a laser micrometer, and the warpage was calculated. The test environment was maintained at a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%. The specimens were preconditioned for 48 hours.

[0032] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.4mm.

[0033] Example 2:

[0034] The difference from Example 1 is that the amount of methyltetrahydrophthalic anhydride is adjusted from 85 parts to 95 parts; the other process parameters are the same as those in Example 1.

[0035] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.2mm.

[0036] Example 3:

[0037] The difference from Example 1 is that the amount of methyltetrahydrophthalic anhydride is adjusted from 85 parts to 105 parts; the other process parameters are the same as those in Example 1.

[0038] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.3mm.

[0039] Example 4:

[0040] The difference from Example 1 is that the phenol-type benzoxazine resin is adjusted from 45 parts to 50 parts; the other process parameters are the same as those in Example 1.

[0041] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.0mm.

[0042] Example 5:

[0043] The difference from Example 1 is that the phenol-type benzoxazine resin is adjusted from 45 parts to 55 parts; the other process parameters are the same as those in Example 1.

[0044] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 1.9mm.

[0045] Example 6:

[0046] The difference from Example 1 is that E51 epoxy resin is replaced by CYD128 epoxy resin; the other process parameters are the same as those in Example 1.

[0047] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.5mm.

[0048] Example 7:

[0049] The difference from Example 1 is that methyltetrahydrophthalic anhydride is replaced by methylnadic anhydride; the other process parameters are consistent with those of Example 1.

[0050] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.3mm.

[0051] Example 8:

[0052] The difference from Example 1 is that phenol-type benzoxazine is replaced by bisphenol A-type benzoxazine; the other process parameters are the same as those in Example 1.

[0053] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.1mm.

[0054] Example 9:

[0055] The difference from Example 1 is that the curing mold temperature is adjusted from 180° C. to 170° C.; the other process parameters are consistent with Example 1.

[0056] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.7mm.

[0057] Example 10:

[0058] The difference from Example 1 is that the curing mold temperature is adjusted from 180° C. to 190° C.; the other process parameters are consistent with Example 1.

[0059] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.0mm.

[0060] Example 11:

[0061] The difference from Example 1 is that the pulling speed is adjusted from 100 mm / min to 80 mm / min; the other process parameters are consistent with those of Example 1.

[0062] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.2mm.

[0063] Example 12:

[0064] The difference from Example 1 is that the pulling speed is adjusted from 100 mm / min to 120 mm / min; the other process parameters are consistent with those of Example 1.

[0065] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.8mm.

[0066] Example 13:

[0067] The difference from Example 1 is that the epoxy resin is E51 and CYD128 mixed in a weight ratio of 50:50; the other process parameters are the same as those in Example 1.

[0068] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.5mm.

[0069] Example 14:

[0070] The difference from Example 1 is that the epoxy resin is a mixture of E51 and E54 in a weight ratio of 70:30; the other process parameters are the same as those in Example 1.

[0071] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.3mm.

[0072] Example 15:

[0073] The difference from Example 1 is that the liquid acid anhydride is a mixture of methyltetrahydrophthalic anhydride and methylnadic anhydride in a weight ratio of 60:40; the other process parameters are the same as those in Example 1.

[0074] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.2mm.

[0075] Example 16:

[0076] The difference from Example 1 is that the benzoxazine resin is a mixture of phenol type and bisphenol A type in a weight ratio of 50:50; the other process parameters are the same as those in Example 1.

[0077] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 1.9mm.

[0078] Example 17:

[0079] The difference from Example 1 is that the epoxy resin is CYD128 and E54 mixed in a weight ratio of 40:60; the other process parameters are the same as those in Example 1.

[0080] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.6mm.

[0081] Example 18:

[0082] The difference from Example 1 is that the liquid acid anhydride is a mixture of methyltetrahydrophthalic anhydride and methylnadic anhydride in a weight ratio of 50:50; the other process parameters are the same as those of Example 1.

[0083] It has been measured that the deformation of the produced modified epoxy insulated I-beam is 2.1mm.

[0084] Comparative Example 1:

[0085] Step 1: Add E51 epoxy resin, methyltetrahydrophthalic anhydride and paraffin wax in a weight ratio of 100 parts:85 parts:1.5 parts into a high-speed mixer, and mix at a speed of 11200-1500 r / min for 5-8 minutes to obtain a uniform resin glue solution.

[0086] Step 2: Pour the resin glue into the 55°C constant temperature impregnation tank of the pultrusion equipment, impregnate the glass fiber with resin at a pulling speed of 100mm / min, and then pass it through a scraper-type preforming mold with a gap of 1.2-1.8mm and a 180°C curing mold.

[0087] C, and naturally cool the product to room temperature to obtain comparative product 1.

[0088] The deformation of Comparative Product 1 was tested using the following method: a 1200mm long specimen was simply supported over a 1000mm span. The mid-span deflection was measured using a laser micrometer, and the warpage was calculated. The test environment was 23°C ± 2°C and 50% ± 5% relative humidity. The specimen was pre-conditioned for 48 hours.

[0089] It was measured that the deformation of the comparative product 1 produced was 4.8 mm.

[0090] Comparative Example 2:

[0091] Step 1: E51 epoxy resin, methyltetrahydrophthalic anhydride, phenolic benzoxazine resin and paraffin are added into a high-speed mixer in a weight ratio of 100 parts: 85 parts: 45 parts: 1.5 parts, and mixed at a speed of 11200-1500 r / min for 5-8 minutes to obtain a uniform resin glue solution.

[0092] Step 2: Pour the resin glue into the mold and perform vacuum degassing (-0.08MPa).

[0093] Step 3: Compression molding, curing conditions are single temperature 180°C, pressure 5MPa, and holding time 30 minutes.

[0094] Step 4: demould the product and cool it naturally to room temperature to obtain comparative product 2.

[0095] The deformation of modified epoxy-insulated I-beams was tested using the following method: 1200mm long specimens were simply supported across a 1000mm span. The mid-span deflection was measured using a laser micrometer, and the warpage was calculated. The test environment was maintained at a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%. The specimens were preconditioned for 48 hours.

[0096] It was measured that the deformation of the comparative product 2 produced was 3.7 mm.

[0097] The comparison table of the results of the embodiment and the comparative example is shown in Table 1:

[0098] Table 1

[0099]

[0100]

[0101]

[0102]

[0103]

[0104] Examples 1-18 demonstrate that by varying the amounts, types, and mixing of the epoxy resin, liquid anhydride, and benzoxazine resin, as well as process parameters, the deformation of the resulting low-deformation modified epoxy insulated I-beams can be controlled within a range of 1.7-3.0 mm. This demonstrates the feasibility of the proposed preparation method under various parameter combinations, and demonstrates the robustness of the overall technical solution, enabling the reliable production of low-deformation products.

[0105] A comparison of Example 1 and Comparative Example 1 clearly demonstrates the crucial role of benzoxazine resin in controlling product deformation. When added to the formulation, benzoxazine resin forms an interpenetrating network with the epoxy resin. Its low shrinkage (only 0.1%-0.3%) effectively inhibits the volume shrinkage of the epoxy resin during curing, significantly reducing the internal stress generated by shrinkage and significantly minimizing deformation in the final product. This strongly supports the necessity of benzoxazine resin as a key modifying component in the claims.

[0106] Regarding process parameters, using Examples 9, 10, 11, and 12 as examples, when the curing temperature deviates from the appropriate range or the pultrusion speed is outside the reasonable range, the product deformation increases accordingly. However, under appropriate process parameters, the product achieves a good curing effect and low deformation. This demonstrates that the process parameters determined by the present invention, such as the heating and curing mold temperature and the pultrusion pulling speed, have been rationally optimized and play a key synergistic role in achieving low product deformation.

[0107] Compared with the case of comparative example 2 which adopts the traditional molding process, the pultrusion process adopted in the present invention is combined with innovative means such as gradient heating and curing, which can better achieve uniform fiber impregnation and arrangement compared with the traditional process, while avoiding the internal stress concentration problem caused by factors such as process discontinuity and uneven cooling, and ultimately achieve a lower deformation.

[0108] Example 19

[0109] Different from Example 1, nano-silicon dioxide is added to the components of this embodiment, and the curing mold adopts a three-stage gradient curing mold.

[0110] The specific steps are as follows:

[0111] A. Prepare raw materials, specifically:

[0112] E51 epoxy resin: 100 parts. The epoxy resin is Nan Ya Resin NPEL-128, with an epoxy equivalent weight of 190 g / eq.

[0113] Benzoxazine resin compounding system: 55 parts. The benzoxazine resin compounding system includes 30 parts of phenol-type benzoxazine and 25 parts of bisphenol A-type benzoxazine.

[0114] Nano-silica filler: 15nm hydrophilic SiO2: 5 parts. The nano-silica filler needs to meet the specific surface area ≥ 400m / g, and the surface is modified with γ-glycidyloxypropyltrimethoxysilane.

[0115] Silicone release agent: 1.5 parts. The silicone release agent is polydimethylsiloxane with a viscosity of 100 mm / s.

[0116] B. Add epoxy resin, compound benzoxazine, and nano-SiO2 into a high-speed mixer, set the speed to 4000 r / min, and premix at 60°C for 10 minutes to evenly disperse the nanoparticles. Detect D50 ≤ 50 nm using a laser particle size analyzer.

[0117] Methyltetrahydrophthalic anhydride and a release agent were added, and the mixture was mixed for 8 minutes, followed by vacuum degassing for 15 minutes to obtain a resin adhesive solution with a bubble rate of less than 0.1%.

[0118] C. The gradient heating curing mold is divided into three sections. The first section is the entrance zone, with a temperature of 160°C ± 2°C and a length of 0.3m, which is used to promote the initial ring opening of benzoxazine. The second section is the middle zone, with a temperature of 180°C ± 2°C and a length of 0.5m, which is used for deep crosslinking of epoxy resin and anhydride and for filling the network pores with nano-SiO2. The third section is the exit zone, with a temperature of 200°C ± 2°C and a length of 0.4m, which is used to ensure complete curing.

[0119] The pulling speed is 100 mm / min, the glass fiber adopts 2400Tex high modulus fiber, the surface of which is treated with KH-550 silane, and the fiber volume fraction is 65%±2%.

[0120] D. After curing, the product is quickly cooled to 50℃ by air cooling, and then naturally cooled to room temperature to avoid thermal stress caused by local temperature differences.

[0121] According to the test, the deformation of the produced modified epoxy insulated I-steel is 1.7mm and the curing degree is 99%.

[0122] In this example, the benzoxazine compounding and nano-SiO2 filling create a synergistic effect, effectively reducing deformation. The gradient temperature setting precisely matches the ring-opening temperature of the compounded benzoxazine, enabling customized design from material reaction characteristics to process parameters. The added nanofiller ensures the product combines the advantages of low deformation, high insulation, and high strength.

[0123] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing low-deformation modified epoxy insulated I-beam, characterized in that: The following steps are involved: A. Add epoxy resin, liquid acid anhydride, benzoxazine resin and silicone release agent in a weight ratio of 100 parts: 85-105 parts: 45-55 parts: 1.5 parts into a high-speed mixer and mix well to obtain a resin glue solution; B. Pour the resin glue into the constant temperature impregnation tank of the pultrusion equipment, pull the glass fiber to be impregnated with resin, and then pass it through the preforming mold and curing mold in sequence; C, cooling the product to room temperature to obtain a modified epoxy insulated I-steel.

2. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: The epoxy resin is any one of E51, CYD128, and E54, or a mixture of any two of them in any ratio.

3. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: The liquid acid anhydride is any one of methyltetrahydrophthalic anhydride and methylnadic anhydride or a mixture of the two in any ratio.

4. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: The benzoxazine resin is any one of a phenol-type benzoxazine resin and a bisphenol A-type benzoxazine resin, or a mixture of the two in any ratio.

5. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: The temperature of the constant temperature immersion tank is 55℃±3℃.

6. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: The mold curing temperature is 180±10℃.

7. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: In step B, the pultrusion pulling speed is 100±20 mm / min.

8. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: The deformation of the modified epoxy insulated I-beam is 1.7-3.0mm.

9. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: Before pouring the resin glue into the constant temperature dipping tank of the pultrusion equipment, the high-speed mixer is vacuumed to maintain the pressure inside the mixer between -0.08MPa and -0.06MPa.

10. The method for preparing a low-deformation modified epoxy insulated I-beam according to claim 1, characterized in that: In step A, the rotation speed of the high-speed mixer is 1200-1500 r / min, and the mixing time is 5-8 minutes.

Citation Information

Patent Citations

  • A two-liquid high-voltage resistant epoxy insulating casting resin and preparation method thereof

    CN119775712A